Good Manufacturing Practice Regulations for Probiotic Based Pharmaceuticals: Current Scenario and Suggestive Recommendations - Arora, Malika; Baldi, Ashish (Applied Clinical Research, Clinical Trials and Regulatory Affairs, 2015)
Background: Usage of probiotic based products has shown a rapid and worldwide growth due to their unlimited therapeutic benefits. Though probiotics are being exploited since ancient times but now a days major issue of concern is their emergence as drugs. In concern to their exponentially increasing market value, their quality, safety and efficacy related affairs are becoming significantly important not only for the consumers rather for manufacturers as well as regulators. As per ongoing scenario, regulatory guidelines stipulating requirements of Good Manufacturing Practice (GMP) are not yet covered properly by any of the country except canada and hence regulatory regimes seems to be highly unsatisfactory. Methods: GMP issues related to probiotic based products were reviewed using secondary sources i.e. electronic databases including Google Scholar, Scopus, Pubmed along with open online resources from journals, market reports, proceedings, books and web pages of relevant regulatory authorities. Later various parameters were critically analyzed for their merits and demerits and future recommendations have been suggested. Results: This paper has been designed to outlook the current regulatory aspects specifically in context to GMP of the probiotic based drug products and to discuss various problematic issues of concern. Above all, the prime aim of the article is to recommend suggestive consolidations to be followed for the manufacturing of the probiotic products. Conclusion: Stringently controlled GMP therefore will remain a most important tool to ensure prescribed standards as well as adequately adopted control measures for meeting finished probiotic products with desired and acceptable quality before their release into market. Suggested recommendations for adopting GMP in production of probiotics in this paper may act as a baseline for regulatory agencies across the globe to formulate the guidelines for the same.
Keywords: qulaity assurance